THE EFFECT OF EXERCISE WITH PERSONAL TRAINER IN FITNESS ONLINE ON HEALTH-RELATED FITNESS - THANAJIRALERTKUL, Doltada; MITRANUN, Witid; PANURUSHTHANON, Phichayavee (Journal of Sports Science and Technology, 2021)
The purposes of this study were to investigate the results of exercise with online fitness trainers on health–related fitness upon maximal oxygen consumption (VO2max), flexibility, body mass index, (percentage of body water, fat free mass, fat mass), strength of the muscles (chest, back, quadriceps and hamstring) there were 20 participants by purposive method. Participants performed exercise with personal trainer in fitness online on 60 minutes, 3 days per week for 12 weeks. VO2max was examined using Modified Bruce Protocol at pre- exercise, after 6 and after 12 weeks. The data was analyzed using means, standard deviation, one-way analysis of variance with repeated measure with statistical significance was set at p value < 0.05 The results found that the before after week 6 and after week 12 showed that the mean values of VO2max, flexibility, body mass index, percentage of body water, fat free mass, fat mass, strength of the muscles of the chest, back, quadriceps and hamstring are tended to improve accordingly. The comparison of the effect of exercise with online fitness trainers on physical fitness for health. With VO2max, flexibility, strength of the muscles of the chest, back, quadriceps and hamstring are tended to improve accordingly. There was a statistically significant difference at the 0.05 level. While the BMI, total body water, fat free mass and fat mass were not statistically different at the 0.05 level. The results of this study clearly prove that exercise with personal in fitness online on program can improving the health-related fitness. (Journal of Sports Science and Technology 2021; 21 (2):100-109) (Received: 3 August 2021 , Revised: 7 December 2021, Accepted: 8 December 2021 2021) Keywords: Personal Trainer / Fitness Online / Health Related Physical Fitness * Corresponding author: Doltada THANAJIRALERTKUL Philosophy Program in Sport and Exercise Science Department of Sport Science, Faculty of Physical Education, Srinakharinwirot University, Thailand E-mail: doltada.dt@gmail.com